For the love of Spock [videorecording (DVD)] - Nimoy, Adam, 1956-; Pine, Chris, 1980-; Saldana, Zoë, 1978-; Urban, Karl, 1972-; Quinto, Zachary; Shatner, William (Film Rise, 2016)
Celebrate the 50th anniversary of Star Trek through a personal, intimate look at the life and career of Leonard Nimoy and the enduring appeal of his alter ego, Mr. Spock, as told by his son, Adam Nimoy.